Mass Killings in the United States from 2006 to 2013: Social Contagion or Random Clusters?. Issue 4 (20th July 2017) - Lankford, Adam; Tomek, Sara
Abstract : In line with previous research on suicide and social contagion, there has been widespread speculation that mass killings—which often involve suicidal offenders—are socially contagious for up to 14 days. This study tested these claims by making comparisons (i) between observed chronological clusters of mass killings in the United States from 2006 to 2013 and clusters in 500 simulations containing 116, 000 randomly generated dates, and then (ii) between observed mass killings receiving varying levels of public attention. No evidence of short‐term contagion was found, although longer term copycat effects may exist. Further scholarly and policy implications are discussed.